A wireless instrumented milling cutter system with embedded PVDF sensors. (15th September 2018) - Luo, Ming; Luo, Huan; Axinte, Dragos; Liu, Dongsheng; Mei, Jiawei; Liao, Zhirong
Highlights: A milling cutter system with embedded thin film sensors in each inserts is proposed. A dedicated milling force decoupling model is proposed and calibrated. Cutting forces on each insert can be monitored without reducing system stiffness. For the first time online estimation of separate inserts' working condition is achieved. Abstract: Among all the monitoring data which could be captured in a machining process, the cutting forces could convey key knowledge on the conditions of the process. When the machining involves a single cutting edge the relationship between the output forces (measured with off-the-shelf dynamometers) and condition of the process, is somehow straight forward. However, when multiple cutting edges are in contact with the workpiece, the conventional dynamometers, that cannot separate the reaction forces on each cutting edge, lose significant information that could be used to in-detail monitor the machining process. To this end, this paper presents a novel concept of instrumented wireless milling cutter system with embedded thin film sensors in each cutting inserts, thus the cutting forces acting on each cutting edge could be monitored without reducing the stiffness and dynamic characteristics of the machining system. For this to happen, a dedicated milling force decoupling model for the developed instrumented milling cutter system is proposed and calibrated, and for the first time the accurate on-line estimation of the separate inserts' working conditions is achieved. The validation demonstrates a satisfactory agreement between the forces measured from the dynamometer and the proposed monitoring system prototype with the error less than 10%. Furthermore, the experimental results also indicate that the monitoring system prototype could also identify the tool insert conditions such as worn and chipped, which could be of high relevance to the analysis of the insert failure mechanism and its progress. Not only the proposed method and easy implementable but above all, it allows the monitoring of the condition (e.g. worn, chipped) of each insert, ability that has not been previously reported.